3, 6-Bis(1-methyl-4-vinylpyridinium)-carbazole diiodide as a marker for tracking living neural stem/precursor cells. Issue 10 (14th March 2015) - Li, Yi-Chen; Wang, Jyh-Horng; Tsai, Li-Kai; Chen, Yun-An; Chang, Ta-Chau; Lou, Pei-Jen; Young, Tai-Horng
<x xml:space="preserve">Abstract</x> A novel compound, 3, 6-bis(1-methyl-4-vinylpyridinium)-carbazole diiodide, is used as a marker for distinguishing living neural stem/precursor cells (NSPCs) from adipose-derived stem cells (ADSCs) and bone marrow mesenchymal stem cells (BMMSCs).